Ductility effect on clinching joint strength in lap-shear configuration loading. (2021) - Kumar, Santosh; Avinash, G.; Vimal, E.
Abstract: Clinching is a mechanical sheet metal joining method in which the sheets are geometrically interlocked using, punch and die, tools without any consumables. In this work, to improve the clinching joint strength in lap shear configuration, the base sheet material is heat-treated in a furnace over varying time durations and temperatures to improve the ductility. Ductility is the prime factor in deciding the amount of cold roll bonding (CRB). This CRB helps during the joining of heat-treated sample to eliminating the gap at the "S" interlock and increase in friction, otherwise the gap would be present in the untreated material. This elimination of gap and higher friction is necessary for the identified belt friction mechanism operating at the lap shear configuration to produce higher joint strength. These causes are confirmed by examining SEM images of the cross sections of the joint and fractography of the failed joint interface. The joints so formed are tested for its strength in monotonic lap-shear configuration loading. Experimentally it is observed that the heat-treatment of base sheets improves the strength in this configuration by more than 50% compared to the untreated material.